Simulation Study on Lightning Impulse Characteristics of Flexible Graphite Composite Grounding Materials Applied to Grounding Grid of Power System - Hu, Yuanchao; Huang, Tao; An, Yunzhu; Feng, Jianyuan; Cheng, Meng; Xie, Hongping; Shen, Wentao; Du, Changqing (Frontiers in Energy Research, 2022)
The flexible graphite composite grounding electrode is a non-metallic grounding electrode with good electrical conductivity, corrosion resistance and non-ferromagnetic properties. In order to analyze the impulse characteristics of the graphite composite grounding electrode, this paper builds a frequency domain electrical network model and an equivalent radius iterative algorithm, considering skin effect, inductance effect, capacitance effect and spark discharge effect. The impulse characteristics of typical metal grounding electrodes and graphite composite grounding electrodes are analyzed by simulation. The research results show that: Compared with the traditional metal grounding electrode, the graphite composite grounding electrode has a smaller skin and inductance effect under the action of the impulse current, and a better current flowing capability; as the soil resistivity increases, the inductance effect and the skin effect are weakened, while the spark discharge effect is gradually enhanced and dominates. The spark discharge effect can effectively decrease the grounding resistance. The obtained critical value of the normalized parameter of 412 kA Ω, can be taken as the threshold to discriminate the conditions with dominate inductance effect from the conditions with dominant spark discharge effect.